The Moderating Effect of Competitive Advantage and Environment on the Relationship of Innovation Practices and Technology Adoption on SME Performance - Imhemad, Imhemad Abdusalam Almahdi (2011)
SMEs are considered as engine for economic growth of most nations. They contribute in providing job opportunities, and act as specialist supplier of components, parts and sub-assemblies to large firms. However, due to global competition, technological advances and changing needs of customers, SMEs are on tremendous pressure to sustain their competitiveness in domestic as well as global markets. Thus, this study was undertaken to determine the influence of certain variables on SME performance in Libya. Specifically, the objectives of study were to (1) determine the relationship between innovation practices and IS capability to SME performance, (2) determine the moderating effect of competitive advantage on the relationship between innovation practice and SME performance, (3) determine the moderating effect of environment on the relationship between innovation practice and SME performance, (4) determine the moderating effect of competitive advantage on the relationship between IS capability and SME performance, and (5) determine the moderating effect of environment on the relationship between IS capability and SME performance. A survey method was employed and questionnaires were used to obtain information from the owner/managers of small and medium plastic firms in Libya. The questionnaire developed by Terziovski (2010) was used to measure innovation practices, while IS capability measurement was based on a previous study by Ravichandran and Lertwongsatien (2005). For competitive advantage, the measurement used a 12 items from Ramaswai, Bhargava and Srivastava (2004), the environment measurement from questions adopted from Thong and Yap (1995) and performance scale was taken from Zhang (2005). A total of 830 owner/managers from the sampling frame were sent with the questionnaires and 179 usable responses were returned giving a response rate of 21.56 percent, which is relatively good. Data were analysed using correlations and multiple regressions to test the relationships. Results revealed that all variables under study had shown significant and positive relationship with performance except a dimension of innovation practice (innovation culture) which did not show any significant relationship with SME performance. Similarly, the moderating effect of both environment and competitive advantage on the relationships between innovation practice and performance, and between IS capability and performance had been supported. The findings of this study suggested that innovation practices and IS capability are important factors for improving performance of SMEs in Libya and to make them more competitive. The study concluded with a discussion of theoretical and practical implications, the study limitations and suggestions for future research.